2004
DOI: 10.1111/j.1399-0039.2004.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex haplotypes in Spanish immunoglobulin A deficiency patients: a comparative fine mapping microsatellite study

Abstract: The most consistent finding in Immunoglobulin A deficiency (IgAD) genetics is the presence of susceptibility factors located in the major histocompatibility complex (MHC). We have described the existence of at least two distinct susceptibility genes in the MHC present in different haplotypes. The aim of the present study was to locate with precision the susceptibility genes present in DR1- and DR7-positive haplotypes, taking advantage of their structural diversity, as opposed to the conserved nature of the DR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…C4 nulls and low subclass levels were not associated in our patient groups [9,42,43]. Total IgG4 deficiency has been found previously together with total C1, C4, C2 and C3 deficiencies, but we found it exclusively in patients without C4A nulls (data not shown) [42,44].…”
Section: Discussionsupporting
confidence: 50%
“…C4 nulls and low subclass levels were not associated in our patient groups [9,42,43]. Total IgG4 deficiency has been found previously together with total C1, C4, C2 and C3 deficiencies, but we found it exclusively in patients without C4A nulls (data not shown) [42,44].…”
Section: Discussionsupporting
confidence: 50%
“…The location of this DIP is consistent with literature evidence of a complex series of deletions and insertions in the region between DRB1 and DQA1 26 and a null allele of the microsatellite D6S2664, which also lies in this region. 27 We could find no evidence that this DIP affected or biased the distribution of alleles in samples that were successfully genotyped for this SNP.…”
Section: Snp Genotyping Perlegenmentioning
confidence: 83%
“…Based on the observation that similar susceptibility effects in partially different haplotypes are due to the region shared among them, a previous study of our group [15] pointed out the region between G51152 and 8105224 microsatellites (the only shared region among all the haplotypes carrying DRB1*0102) as the one harboring the causal gene. However, with the inclusion of the MSH5 L85F polymorphism in the study, it is observed that only a subgroup of those DRB1*0102-carrying haplotypes increases the risk to IgAD and therefore that common region (between G51152 and 8105224) can be ruled out as the carrier of the susceptibility factor.…”
Section: Discussionmentioning
confidence: 98%
“…DRB1 was typed by polymerase chain reaction (PCR), followed by hybridization with allele-specific probes [3] and DRB1*1501 and HLA-B*08 by TaqMan technology using the highly correlated SNPs rs3135388 (DRB1*1501), rs6457374, and rs2844535 (HLA-B*08). Moreover, information from additional HLA markers or loci, obtained in our laboratory as previously described [3,15], was used for the available samples (83 trios). These additional markers include 16 microsatellites located in (or close to) different genes located in major histocompatibiliy complex (MHC) class III and class II: MICA, TNFa, TNFb, BAT2, D6S273, 9N2, MN6S1424, D6S2670, D3A, NOTCH4, 8105224, D6S2665, D6S2664, DQCARII, DQCAR, G51152, and the polymorphic genes HLA-B (class I) and DQA1 and DQB1 (class II).…”
Section: Methodsmentioning
confidence: 99%